CRIMINAL POLICY REINTEGRATION BY ANTI-EARLY EDUCATION POLICY CORRUPTION TO ERADICATE CORRUPTION IN REGIONS - ABNAN PANCASILAWATI (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
Corruption has developed into an extra ordinary crime and is increasingly massive at every level of government. Local autonomy that has been actually intended to decentralized the administration of government to realize a clean and authoritative government (clean and good governance) actually becomes an arena of decentralization of corrupt behavior. Up to now (since 2004), there have been 434 local heads who have been prosecuted for alleged corruption and other law violations, and 70% have been found guilty. If so, it needs an integrative effort in its eradication by reintegrating criminal policy with anti-corruption early education policies.